Personalized Adaptive Training Improves Performance at a Professional First-Person Shooter Action Videogame - Neri, Francesco; Smeralda, Carmelo Luca; Momi, Davide; Sprugnoli, Giulia; Menardi, Arianna; Ferrone, Salvatore; Rossi, Simone; Rossi, Alessandro; Di Lorenzo, Giorgio; Santarnecchi, Emiliano (Frontiers in Psychology, 2021)
First-Person-Shooter (FPS) game experience can transfer to untrained cognitive functions such as attention, visual short-term memory, spatial cognition and decision-making. However, previous studies have been using off-the-shelf FPS version based on predefined gaming settings, so it is not known whether such improvement can be maximized by customizing the in-game training. To address this question, we compared the impact of a popular FPS-game (Counter-Strike:Global-Offensive–CS:GO) with an ad-hoc, personalized training based on an adaptive algorithm specifically based on gaming performance. Two groups of naïve healthy young participants were randomly assigned in playing one of the two game versions (11 and 10 subjects, respectively), two hours/day for three weeks in a controlled laboratory setting, including daily in-game performance monitoring, as well as extensive cognitive evaluations administered before, immediately after, and 3 months after the training. Participants exposed to the adaptive version of the game were found to progress significantly faster in terms of in-game performance, reaching gaming scenarios up to 2.5 times more difficult than the group exposed to standard CS:GO. A significant increase in general cognitive performance, beyond gaming abilities, was also observed. Personalized FPS gaming can significantly speed-up the learning curve of naïve action videogame-players, with possible future applications for expert-video-gamers and potential relevance for clinical-rehabilitative applications.